A novel technique for accurate electrode placement over cortical targets for transcranial electrical stimulation (tES) clinical trials. (11th October 2021) - Jog, Mayank; Anderson, Cole; Kim, Elizabeth; Garrett, Avery; Kubicki, Antoni; Gonzalez, Sara; Jann, Kay; Iacoboni, Marco; Woods, Roger; Wang, Danny JJ; Narr, Katherine L
Abstract: Objective . We present an easy-to-implement technique for accurate electrode placement over repeated transcranial electrical stimulation (tES) sessions across participants and time. tES is an emerging, non-invasive neuromodulation technique that delivers electrical stimulation using scalp electrodes. Approach. The tES electrode placement technique was developed during an exploratory clinical trial aimed at targeting a specific MNI-atlas cortical coordinate in N = 59 depressed participants (32 F, mean age: 31.1 ± 8.3 SD). Each participant completed 12 sessions of active or sham stimulation, administered using high-definition (HD) or conventional sized electrode montages placed according to the proposed technique. Neuronavigation data measuring the distances between the identified and the intended stimulation site, simulations, and cerebral blood flow (CBF) data at baseline and post-treatment were acquired to evaluate the targeting characteristics of the proposed technique. Main results. Neuronavigation measurements indicate accurate electrode placement to within 1 cm of the stimulation target on average across repeated sessions. Simulations predict that these placement characteristics result in minimal electric field differences at the stimulation target (>0.90 correlation, and <10% change in the modal electric field and targeted volume). Additionally, significant changes in %CBF (relative to baseline) under the stimulation target in the active stimulation group relative to sham confirmed that the proposed placement technique introduces minimal bias in the spatial location of the cortical coordinate ultimately targeted. Finally, we show proof of concept that the proposed technique provides similar accuracy of electrode placement at other cortical targets. Significance. For voxel-level cortical targets, existing techniques based on cranial landmarks are suboptimal. Our results show that the proposed electrode placement approach provides high consistency for the accurate targeting of such specific cortical regions. Overall, the proposed technique now enables the accurate targeting of locations not accessible with the existing 10–20 system such as scalp-projections of clinically-relevant cortical coordinates identified by brain mapping studies. Clinical trial ID: NCT03556124.